Buying and Selling Mystical Oil According to Central Kalimantan Scholars - Madina, Ahya; Rahmaniah, Amelia (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
The trade in mystical oil is a phenomenon that exists in society, one example being in Central Kalimantan, particularly in the city of Kuala Kapuas. This practice has raised doubts among the community regarding its legitimacy. Therefore, this study aims to explore the opinions of religious scholars in Kuala Kapuas and the arguments they use. This is an empirical legal study involving interviews with five religious scholars from the Indonesian Ulema Council (MUI) and the Majelis Ta’lim. The results of the study indicate that the religious scholars are divided into two groups: the first group permits the buying and selling of mystical oil provided it meets the legal requirements of Islam, while the second group prohibits it, as it is considered to involve elements of fraud and the potential for idol worship.